2017
DOI: 10.1098/rspb.2016.2406
|View full text |Cite
|
Sign up to set email alerts
|

Support for the reproductive ground plan hypothesis in a solitary bee: links between sucrose response and reproductive status

Abstract: In social bees, foraging behaviour is correlated with reproductive status and sucrose sensitivity via endocrine pathways. This association led to the hypothesis that division of labour in social insect societies is derived from an ancestral ground plan that functions to synchronize dietary preferences with reproductive needs in solitary insects. However, the relationship between these traits is unknown for solitary bees, which represent the ancestral state of social bees. We used the proboscis extension respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 81 publications
1
25
0
Order By: Relevance
“…Seminal fluid is known to trigger oogenesis in several 252 insect species (Avila et al, 2011), and mating limitation is known to influence reproductive activity in other halictid bees (Yanega, 1989;Yanega, 1992). However, lab-reared females of another halictid bee, (Kapheim et al, 2012). If mating is a reproductive limitation in alkali bees, it can apparently be 256 overridden by JH treatments, as some JH-treated females in our study reached reproductive maturity, 257 even in the absence of mating or ecological cues.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Seminal fluid is known to trigger oogenesis in several 252 insect species (Avila et al, 2011), and mating limitation is known to influence reproductive activity in other halictid bees (Yanega, 1989;Yanega, 1992). However, lab-reared females of another halictid bee, (Kapheim et al, 2012). If mating is a reproductive limitation in alkali bees, it can apparently be 256 overridden by JH treatments, as some JH-treated females in our study reached reproductive maturity, 257 even in the absence of mating or ecological cues.…”
mentioning
confidence: 72%
“…Little is known about the factors that influence alkali bee reproductive development. However, a recent 68 study demonstrated that JH accelerates reproductive maturation (Kapheim and Johnson, 2017). It was 69 also recently documented that adult female alkali bees consume pollen on a daily basis (Cane et al, 70 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides basic work on comparative cognition, FMPER's potential for assessing gustatory responsiveness (similar to Ma, Kessler, Simpson, & Wright, ) is relevant to many aspects of bee biology (Scheiner et al., ), including tests of hypotheses relating to the evolution of sociality (e.g. the reproductive ground plan hypothesis: Kapheim & Johnson, ).…”
Section: Discussionmentioning
confidence: 99%
“…The second main protocol used to study cognition in insects is the “Proboscis Extension Response (PER) protocol” (honeybees: Bitterman, Menzel, Fietz, & Schäfer, ; Takeda, ; bumblebees: Laloi et al., ; Riveros & Gronenberg, ; fruitflies: Tully & Quinn, ; mosquitoes: Tomberlin, Rains, Allan, Sanford, & Lewis, ; moths: Daly & Smith, ; stingless bees: Mc Cabe et al., ; solitary bees: Kapheim & Johnson, ; hymenopterous parasitoids: Kaiser, Pérez‐Maluf, Sandoz, & Pham‐Delègue, ). In the PER protocol, a bee is harnessed (only its antennae and proboscis free to move [Figure b]), before being trained to an association between a CS and US.…”
Section: Introductionmentioning
confidence: 99%